Bretherick's handbook of reactive chemical hazards. - Urben, P. G.; Pitt, Martin J. 1948-; Bretherick, L. (Elsevier, 2007)
Collects various reported risks such as explosion, fire, toxic or high-energy events that result from chemical reactions gone astray. This title is designed to improve safety in laboratories that perform chemical synthesis and general research, as well as chemical manufacturing plants. It focuses on reactivity risks of chemicals.